The Concept of Strategy in Community Empowerment: A Literature Review - Malta (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Empowerment is a planned effort designed to change or reform an individual or community/society from a state of powerlessness to become empowered with an emphasis on independence. This study aims to be able to see how strategies can be carried out to empower the community. This research was conducted using a descriptive qualitative approach. The research data used in this study came from various previous studies and research results obtained through the literature study method. The results of this study then found that community empowerment is an approach that aims to change conditions of powerlessness to become empowered through increasing independence and active participation. This concept involves providing access to resources, knowledge, and skills to the community so that they can take a role in managing development and determining their future direction. Although different challenges and contexts need attention, empowerment remains an important key in achieving sustainable development.